BIMBINGAN AGAMA PADA ANAK USIA DINI - Syarifuddin, Syarifuddin (Alhadharah: Jurnal Ilmu Dakwah, 2017)
With regard to the potential religious trends of monotheism (Islam) that is owned by every child, so to keep children from getting out of Islam to become Christians, Jews and Majusi. In order not to happen the destruction of the nation due to moral depravity due to negative flow of information and technology advances, so that children are always obedient to Allah and His Messenger, it should be guided and educated about the teachings of Islam on children as early as possible. Every child is born in a state of fitrah, that is the tendency of children to recognize the existence of the Creator, and bring the potentials of self, including the potential in religion. Early childhood ranging from 0-6 years is a golden age for children to determine the direction of the childs life forward. Therefore, in order for the child to remain in his nature, religious guidance in accordance with his psychic development is necessary. The right way to do religious guidance in early childhood, which is to teach good words, avoid dirty words, keep promises, not lie, train memorize sentences thayyiba and that is no less important is a model example for children.